Odpowiedzi

2009-10-29T14:15:26+01:00
25(x-1)2-9(x+2)2=0
25(x²-2)-9(x²+4)=0
25x²-50-9x²-36=0
25x²-9x²=36+50
16x²=86/:16
x²=5,4/√
x=√5,4
2 1 2
2009-10-29T14:19:21+01:00
25(x-1)2 - 9(x+2)2=0
25(x2 - 1) - 9(x2+4)=0
25x2-25-9x2-36=0
16x2 - 61 =0
16x2=61
x=√3,8125
1 1 1
Najlepsza Odpowiedź!
2009-10-29T14:28:01+01:00
25(x-1)²-9(x+2)²=0
25(x²-2*x*1+1²)-9(x²+2*x*2+2²)=0
25(x²-2x+1)-9(x²+4x+4)=0
25x²-50x+25-9x²-36x-36=0
16x²-86x-11=0

Δ=b²-4ac
Δ=(-86)²-4*16*(-11)
Δ=7396+704
Δ=8100
√Δ=90

x₁=-b-√Δ/2a x₂=-b+√Δ/2a

x₁=86-90/36 x₂=86+90/36

x₁=-1/9 x₂=4 i 8/9

/ ---->kreska ułamkowa


-2x+3x>2
x>2
x∈(2,+∞)


Moi poprzednicy nie zastosowali wzorów skróconego mnożenia więc ich rozwiązania są złe.




2 2 2